A low filtration resistance three-dimensional composite membrane fabricated via free surface electrospinning for effective PM2.5 capture. Issue 4 (21st February 2017) - Gao, Hanchao; Yang, Yuqiong; Akampumuza, Obed; Hou, Jue; Zhang, Hongnan; Qin, Xiaohong
Abstract : A low-resistance nanofibrous composite membrane composed of ternary structures was fabricated via one-step multi-jet free surface electrospinning for effective PM2.5 capture. Abstract : Ambient particulate matter (PM) pollution jeopardizes both the global climate and public health. Therefore, there is a need for a cost-effective and energy-efficient air filter. Herein, a low filtration resistance polyacrylonitrile (PAN) three-dimensional composite membrane with high porosity was controllably fabricated via multi-jet free surface electrospinning. The composite nanofibrous membrane, composed of ternary structures including scaffold nanofibers, microspheres and thin nanofibers, was demonstrated as an air filter for the first time. The scaffold nanofibers constituted a stable skeletal framework in which the microspheres were embedded; the microspheres enlarged the inter-fiber voids thus greatly reducing the pressure drop, while thin nanofibers with diameters of 84 nm interwoven with the scaffold nanofibers improved the collision probability of the airborne particles and guaranteed a robust filtration performance without sacrificing filtration efficiency. Additionally, the embedded microspheres also significantly improved the mechanical properties of the membrane. The fabricated high porosity three-dimensional composite membrane exhibited high filtration efficiency (99.99%) and low pressure drop (126.7 Pa) to sodium chloride (NaCl) aerosol particles under an airflow velocity of 5.3 cm s −1 . Furthermore, the as-prepared membrane demonstrated high PM2.5 filtration efficiency (99.24%) in a dynamic PM2.5 filtration system simulating the typical operation environment of an air filter. The low resistance three-dimensional composite membrane fabricated via free surface electrospinning is not only efficient for laboratory research but can also be applied to industrial production and in commercial applications.